EVALUATING MULTI DIMENSIONAL SUSTAINABILITY OF COFFEE FARMER GROUPS: INTEGRATING ENVIRONMENTAL, SOCIO-ECONOMIC, AND GOVERNANCE PERSPECTIVES - Sukron Romadhona; Sumarlin (Jurnal Kommunity Online, 2026)
The dominance of smallholder-based coffee production systems, accounting for more than 94% of plantation areas, highlights both their strategic role and vulnerability within global value chains, particularly under traditional and asymmetric marketing structures. This study aims to assess the sustainability performance of smallholder coffee farming and examine the role of rural small-to-medium coffee industries in strengthening socio-economic and environmental outcomes. Research employs a quantitative-descriptive approach using the Sustainability Assessment of Food and Agriculture systems (SAFA) framework. Data were collected through purposive sampling of coffee farmers in Kalibening and Karangkobar sub-districts, supported by field observations and structured interviews. Findings reveal a heterogeneous sustainability profile. In Kalibening, strong performance is observed in holistic management (85%) and social equity (85%), while weaknesses persist in materials and energy efficiency (30%) and governance aspects such as accountability and participation (50%). In Karangkobar, economic resilience is notably high (85%), supported by strong local investment, yet governance (30–45%) and environmental indicators (45%) remain limited due to conventional farming practices and weak institutional oversight. The novelty of this study lies in integrating SAFA analysis with emerging rural agro-industry dynamics, highlighting their role as catalysts for value addition and improved farmer bargaining power. In conclusion, while socio-economic dimensions show promising progress, strengthening governance systems and promoting environmentally sustainable practices are critical for achieving holistic coffee sustainability